Outcomes of non-small cell lung cancer patients with non-V600E BRAF mutations: a series of case reports and literature review - Lazar, Raluca; Fischbach, Cathie; Schott, Roland; Somme, Laura (Frontiers in Oncology, 2024)
Non-small cell lung cancer (NSCLC) is the most prevalent form of lung cancer, accounting for approximately 85% of cases of lung cancer. The standard first-line therapy for patients without oncogenic driver metastatic NSCLC is anti PD-L1 immune checkpoint inhibition (ICI) with platinum-based chemotherapy. Approximately 4% of NSCLC patients harbor BRAF mutations; the V600E mutation is the most common. Non-V600 mutations is an heterogeneous population and account for approximately 50% of BRAF-mutated NSCLC. BRAF mutations are classified into 3 functional classes based on their kinase activity and their signaling mechanism. The European Medicines Agency and the United States Food and Drug Administration have approved dabrafenib, an anti-BRAF tyrosine kinase inhibitor (TKI), in combination with trametinib, an anti-MEK TKI, for the treatment of patients with BRAF V600E-mutated metastatic NSCLC. The use of targeted therapies in NSCLC with BRAF non-V600E mutations remains controversial. There is a lack of guidelines regarding therapeutic options in non-V600E BRAF-mutated NSCLC. Herein, we presented 3 cases of NSCLC with BRAF non-V600E mutations and reviewed the current state of therapies for this particular population of lung cancer.